2008
DOI: 10.1016/j.ibmb.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to malathion in the medfly Ceratitis capitata

Abstract: Target site insensitivity and metabolic resistance mediated by esterases have been previously suggested to be involved in resistance to malathion in a field-derived strain (W) of Ceratitis capitata. In the present study, we have obtained the coding sequence for acetylcholinesterase (AChE) gene (Ccace) of C. capitata. An allele of Ccace carrying only a point mutation Gly328Ala (Torpedo numbering) adjacent to the glutamate of the catalytic triad was found in individuals of the W strain. Adult flies homozygotes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
18

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 46 publications
3
45
0
18
Order By: Relevance
“…However, interference of ace genes in H. armigera (nonspecific silencing, as in L. migratoria) did affect larval growth and development (Kumar et al, 2009). In fact, insects bearing mutated AChE can show a 40e60% reduction of AChE activity with no effect on survival (Magaña et al, 2008). The reason why CPB or H. armigera may be affected by a reduction of AChE activity more than other insects may be related to the disparity of AChE activity detected in different orders due to variations in expression, specific activity of the enzymes, enzyme availability, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, interference of ace genes in H. armigera (nonspecific silencing, as in L. migratoria) did affect larval growth and development (Kumar et al, 2009). In fact, insects bearing mutated AChE can show a 40e60% reduction of AChE activity with no effect on survival (Magaña et al, 2008). The reason why CPB or H. armigera may be affected by a reduction of AChE activity more than other insects may be related to the disparity of AChE activity detected in different orders due to variations in expression, specific activity of the enzymes, enzyme availability, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Control of medfly populations is mainly based on the use of insecticides. However, resistance to malathion has been reported in field populations (Magaña et al, 2007(Magaña et al, , 2008, showing as well cross-resistance to different insecticides (lambdacyhalothrin, methyl-chlorpyrifos, and lufenuron) currently approved for the control of C. capitata (CousoFerrer et al, 2011). In this context, the improvement of diagnostic procedures for the determination of genetic structure of populations, as well as the gene flow among different geographic areas have a practical application in integrated control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Magaña et al (2008) found that a single-point mutation in acetylcholinesterase in Ceratitis capitata is associated with malathion resistance. Bioinsecticides, such as neem oil, work only on the 1st-instar larvae and reduce the hatching of D. saccharalis eggs (Tavares et al, 2010).…”
Section: Resultsmentioning
confidence: 99%